Constitutional mismatch repair deficiency syndrome with atypical features caused by a homozygous MLH1 missense variant (c.1918C>A, p.(Pro640Thr)): a case report - Akrout, Firas; Achour, Ahlem; Tops, Carli M. J.; Gallon, Richard; Meddeb, Rym; Achoura, Sameh; Ben Rekaya, Mariem; Hamdeni, Emna; Rammeh, Soumaya; Chkili, Ridha; Mansouri, Nada; Belguith, Neila; et al. (Frontiers in Oncology, 2023)
Constitutional mismatch repair deficiency (CMMRD) syndrome is a rare autosomal recessive genetic disorder caused by biallelic germline mutations in one of the mismatch repair genes. Carriers are at exceptionally high risk for developing, typically in early life, hematological and brain malignancies, as well as cancers observed in Lynch syndrome. We report a homozygous MLH1 missense variant (c.1918C>A p.(Pro640Thr)) in a Tunisian patient with CMMRD syndrome and a family history of early-age colorectal cancer. The proband presented initially with colonic oligopolyposis and adenosquamous carcinoma of the caecum. He later developed several malignancies, including undifferentiated carcinoma of the parotid, grade 4 IDH-mutant astrocytoma, and ampulla of Vater adenocarcinoma. The patient was older than typical for this disease and had a remarkably prolonged survival despite developing four distinct aggressive malignancies. The current report highlights the challenges in assessing the pathogenicity of the identified variant and the remarkable phenotypic diversity in CMMRD.